A comparison of haploidentical versus HLA-identical sibling outpatient hematopoietic cell transplantation using reduced intensity conditioning in patients with acute leukemia - Jaime-Pérez, José Carlos; Valdespino-Valdes, Jorge; Gómez-De León, Andrés; Barragán-Longoria, Renata Valeria; Dominguez-Villanueva, Adriana; Cantú-Rodríguez, Olga Graciela; Gutiérrez-Aguirre, César Homero; Gómez-Almaguer, David (Frontiers in Immunology, 2024)
Background. Hematopoietic cell transplantation (HCT) increases survival for acute leukemia. Outpatient allogeneic HCT reduces costs and increases transplant rates in developing countries. We report outcomes of outpatient HLA-identical and haploidentical HCT in acute leukemia. Methods. This single-center retrospective cohort study analyzed 121 adult patients with acute myeloblastic (AML) and acute lymphoblastic leukemia (ALL) receiving an outpatient allogeneic HCT with peripheral blood allografts after reduced-intensity conditioning (RIC) from 2012-2022. Results. There were 81 (67%) haploidentical and 40 (33%) HLA-identical transplants. Complete chimerism (CC) at day +100 was not different in HLA-identical compared to haploidentical HCT (32.5% and 38.2%, P=0.054). Post-HCT complications, including neutropenic fever (59.3% vs. 40%), acute graft-versus-host-disease (aGVHD) (46.9% vs. 25%), cytokine release syndrome (CRS) (18.5% vs. 2.5%), and hospitalization (71.6% vs 42.5%) were significantly more frequent in haploidentical HCT. Two-year overall survival (OS) was 60.6% vs. 46.9%, (P=0.464) for HLA-identical and haplo-HCT, respectively. There was no difference in the 2-year disease-free-survival (DFS) (33.3% vs. 35%, P=0.924) between transplant types. In multivariate analysis, positive measurable residual disease (MRD) at 30 days (HR 8.8, P=0.018) and 100 days (HR 28.5, P=0.022) was associated with lower OS, but not with non-relapse mortality (NRM) (P=0.252 and P=0.123, univariate). In univariate analysis, both 30-day and 100-day MRD were associated with lower DFS rates (P=0.026 and P=0.006), but only day 30 MRD was significant in multivariate analysis (P=0.050). In the case of relapse, only MRD at day 100 was associated with increased risk in the univariate and multivariate analyses (HR 4.48, P=0.003 and HR 4.67, P=0.008). Chronic graft-versus-host-disease (cGVHD) was protective for NRM (HR 0.38, P=0.015). There was no difference in cumulative incidence of relapse (CIR) between transplant types (P=0.126). Forty-four (36.4%) patients died, with no difference between HCT type (P=0.307). Septic shock was the most frequent cause of death with 17 cases, with no difference between transplant types. Conclusions. Outpatient peripheral blood allogenic HCT after RIC is a valid and effective alternative for adult patients suffering acute myeloblastic or lymphoblastic leukemia in low-income populations.